2017
DOI: 10.1016/j.gore.2017.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Efforts towards erasing borders in gynecologic cancer?

Abstract: HighlightsCervical cancer is the second most common cancer among women in LMIC.Major efforts to improve research in gynecologic cancer in LMIC are needed.GOR provides a platform featuring research and review of cancer care in LMIC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…In 2020, there were 604,127 cervical cancer cases and 341,831 deaths worldwide, and 84% of all new cases and 88% of all deaths occur in low- and middle- income countries (LMIC) Chuang et al, 2017 , International Agency for Research on Cancer, 2020 . Although screening and comprehensive treatment are widely available in the United States, Canada, Western Europe, Australia, New Zealand, and many Pacific rim countries, LMIC face unique challenges in providing women with screening and treatment for cervical cancer.…”
Section: Introductionmentioning
confidence: 99%
“…In 2020, there were 604,127 cervical cancer cases and 341,831 deaths worldwide, and 84% of all new cases and 88% of all deaths occur in low- and middle- income countries (LMIC) Chuang et al, 2017 , International Agency for Research on Cancer, 2020 . Although screening and comprehensive treatment are widely available in the United States, Canada, Western Europe, Australia, New Zealand, and many Pacific rim countries, LMIC face unique challenges in providing women with screening and treatment for cervical cancer.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, studies have shown that the use of primary HPV testing, as compared with cytology alone, significantly lowers the likelihood of the development of precancerous lesions among women undergoing cervical cancer screening, due to increased sensitivity and specificity of cytology testing when restricted to only those women who test positive for HPV 16. In addition, some countries are beginning to implement self-collection HPV testing to increase accessibility to screening 17. Women can test themselves, in their own home, by collecting a cervical sample using a provided swab 18.…”
Section: Introductionmentioning
confidence: 99%